VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Wang, Haiyan (Plant science : an international journal of experimental plant biology, 2025)
Copyright © 2025 Elsevier B.V. All rights reserved.